Optimalisasi Maharah Kalam Melalui Metode Muhawarah dalam Pembelajaran Bahasa Arab: Penelitian - Rosyidatul Khoiriyah; Winda Permata Sari; Qurrotul A’ini; Nafisatul Fuadah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Madrasah Aliyah Miftahul Ulum is a school within the Miftahul Ulum Islamic boarding school, an educational institution that focuses on learning Arabic. In practice, Arabic language learning is greatly assisted by the muhawarah method, which is one of many methods used to support the realization of Arabic language learning outcomes, especially in the category of Arabic speaking skills. In addition to the need for a habit of speaking in Arabic, vocabulary is very important in speaking skills. The muhawarah method is said to be more optimal in improving speaking skills. This method aims to improve students' ability to use existing vocabulary and train students' courage in expressing their opinions. The method applied by the researcher in this study is a descriptive qualitative method whose sources of information are obtained from observations during the process of learning speaking skills using the muhawarah method and also the results of interviews with teachers and students. Data analysis applied uses triangulation analysis of data sources that seek the validity of certain information by using various data sources including documents, interview results, observation results or by interviewing more than one subject who is assumed to have different perspectives.